Neuronal Injury and Glial Changes Are Hallmarks of Open Field Blast Exposure in Swine Frontal Lobe. - Srinivasu Kallakuri (PLoS ONE, 2017)
With the rapid increase in the number of blast induced traumatic brain injuries and associated neuropsychological consequences in veterans returning from the operations in Iraq and Afghanistan, the need to better understand the neuropathological sequelae following exposure to an open field blast exposure is still critical. Although a large body of experimental studies have attempted to address these pathological changes using shock tube models of blast injury, studies directed at understanding changes in a gyrencephalic brain exposed to a true open field blast are limited and thus forms the focus of this study. Anesthetized, male Yucatan swine were subjected to forward facing medium blast overpressure (peak side on overpressure 224-332 kPa; n = 7) or high blast overpressure (peak side on overpressure 350-403 kPa; n = 5) by detonating 3.6 kg of composition-4 charge. Sham animals (n = 5) were subjected to all the conditions without blast exposure. After a 3-day survival period, the brain was harvested and sections from the frontal lobes were processed for histological assessment of neuronal injury and glial reactivity changes. Significant neuronal injury in the form of beta amyloid precursor protein immunoreactive zones in the gray and white matter was observed in the frontal lobe sections from both the blast exposure groups. A significant increase in the number of astrocytes and microglia was also observed in the blast exposed sections compared to sham sections. We postulate that the observed acute injury changes may progress to chronic periods after blast and may contribute to short and long-term neuronal degeneration and glial mediated inflammation.